The Influence of the Problem-Based Learning (PBL) Model on the Learning Motivation in Science and Social Studies (IPAS) of Fifth Grade Students at UPTD SD Negeri 12 Parepare - Muhammad Alfitrah Kaharuddin; Musfirah, Musfirah; Yulia, Yulia; Imron Burhan (International journal of technology and education research, 2025)
This study aims to evaluate the effect of the Problem-Based Learning (PBL) model on the learning motivation in Science and Social Studies (IPAS) among fifth-grade students at UPTD SD Negeri 12 Parepare. The study was motivated by the low level of student motivation, particularly in IPAS subjects. A quantitative approach was employed using a Nonequivalent Pretest-Posttest Control Group Design. The research population consisted of 174 students, with a sample of 40 students divided into a control class (20 students from class VA) and an experimental class (20 students from class VB). Data were collected through a learning motivation questionnaire administered during both the pretest and posttest. Data analysis was conducted using descriptive and inferential statistics. The descriptive analysis showed that the experimental class obtained a higher average score (67.8) compared to the control class (61.15). Inferential analysis using the Independent Sample T-Test produced a significance value of 0.001 < 0.05. Based on these results, it can be concluded that the Problem-Based Learning (PBL) model has a significant effect on increasing students’ learning motivation in IPAS.